Planeación de trayectorias de un Robot para la limpieza de paneles solares fotovoltaicos basado en el método Probabilistic Roadmap (PRM) - Leal Ramirez, Leidy Stefanny; Velandia Bejarano, Nelson Stiveen (Universidad Antonio Nariño, 2022)
In this project a navigation system of a cleaning robot was designed to generate cleaning paths in solar panels. The methodology that is carried out in chapter three, where in the first part the graphic environment is designed posing five scenarios using the Inventor tool, then the traction mechanism was designed to perform the displacement on irregular surfaces, finally, the navigation system was designed using the PRM method using Matlab’s software for the planning of trajectories in the different working environments, all with the aim of a future implementation of a solar panel cleaning robot, It should be noted that the validation process was carried out during the development of each of the proposed activities. Where the principles of design and control are used, to achieve the results obtained in chapter four, evidencing the navigation system running the trajectory on the graphic environment for each of the proposed scenarios.